Chylothorax caused by blunt chest trauma: a review of literature - Kakamad, Fahmi Hussein (Indian J Thorac Cardiovasc Surg, 2020)
Chylothorax is the accumulation of chyle in the pleural cavity that typically contains a high concentration of triglycerides. Blunt chest trauma is a rare cause. The aim of this study is to review all of the reported cases of chylothorax caused by blunt chest trauma. Available databases were explored systematically for the condition and the eligible papers were included. The literature search revealed 30 studies with 39 cases, 72.3% of the cases were male, and 21.7% of the patients were female. The age range varied between 4 and 75 years with a mean age of 35.8 years. All of the patients were diagnosed after fluid sampling from the pleural fluid by thoracentesis and/or chest tube insertion. About 71.4% of the patients were treated successfully by conservative management: others (28.6%) were managed surgically. Although it is a rare condition, persistent milky drainage after blunt chest trauma should raise the suspicion of chylothorax. Pleural fluid sampling is the cornerstone of the diagnosis. In the majority of the cases, conservative treatment is quite enough. Surgery is indicated whenever non-operative measures failed.